Social Segregation in Hong Kong's Schools: 2000–2012. Issue 3 (2nd July 2016) - Zhou, Yisu; Cai, Tianji; Wang, Dan
Abstract: This article examines the distribution of students from various socioeconomic backgrounds across secondary schools in Hong Kong. Using data from the Program for International Student Assessment over the past decade, we computed axionomical indices of social segregation for 15-year-old students. The degree of social segregation in Hong Kong is compared with three other Chinese societies: Macau, Taiwan, and Shanghai. We found that social segregation steadily increased during 2000–2012. Hong Kong has the highest level of social segregation in schools among the four regions. The degree of segregation remains relatively stable among the top and bottom student socioeconomic status (SES) groups while substantially spread out among middle SES groups. Two factors were found to drive social segregation: gentrification of elite private schools, and the creation of semi-private schools for the upper middle class. Our findings suggest increasingly dividing education experiences among Hong Kong's youth.